COVERING THE REALITIES OF THE KHIVA KHANATE AND THE KHANS OF THE XIX CENTURY IN THE HISTORICAL WORKS OF AGAKHI (TAMADDUN NURI JURNALI, 2024)
In the article the authors provide information about the coverage of historical events related to the Khanate and khans of Khiva XIX century, in the historical works of Agakhi.